The challenging pathway towards the identification of SARS-CoV-2/COVID-19 therapeutics. (26th June 2020) - Siccardi, Marco; Schapiro, Jonathan; Di Perri, Giovanni; Back, David J
Abstract: The development of therapeutic agents against SARS-CoV-2/COVID-19  faces numerous barriers and a multidisciplinary approach to evaluating drug efficacy and toxicity is essential. Experimental and preclinical data should be integrated into a comprehensive analysis, where drug potency, the timing of therapy initiation, drug combinations, variability in systemic and local drug exposure and short- and long-term toxicities represent fundamental factors for the rational identification of candidates and prioritization of clinical investigations. Although the identification of SARS-CoV-2 therapeutics is a priority, rigorous and transparent methodologies are crucial to ensure that accelerated research programmes result in high-quality and reproducible findings.